Arthropods Are They Beneficial for Mankind? - Eduardo Rebolledo Ranz, Ramón (IntechOpen, 2021)
This book presents comprehensive information on arthropods, the most abundant and diverse group of invertebrate animals in existence today. Chapters cover such topics as arthropods as food for humans, arthropods as a bioindicator species, use of arthropods in the cosmetic and pharmaceutical industries, arthropods and their conservation status, diets for raising arthropods, and much more. It is a useful reference for undergraduate and graduate students, academics, researchers, and anyone interested in learning more about this important group of invertebrates and their current conservation status.